Girsanov theorem for stochastic flows with interaction - Malovichko, T. V. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We prove an analog of the Girsanov theorem for the stochastic differential equations with interaction$$dz(u,t) = a(z(u,t),μt)dt + ∫R f(z(u,t)−p)W(dp,dt),$$where $W$ is a Wiener sheet on $ℝ × [0; +∞)$ and $a(∙)$ is a function of special type.